Retrospective study into the delivery of telephone cardiopulmonary resuscitation to "999" callers. Issue 2 (26th February 2004) - Heward, A; Donohoe, R T; Whitbread, M
Abstract : Background: Cardiopulmonary resuscitation (CPR) is an essential part of the chain of survival, with early administration directly affecting the patient's chance of survival. Pre-arrival telephone CPR instructions provide callers who have no CPR training on how to undertake this intervention. With the emergency medical dispatcher unable to see the caller or the patient, it is possible that problems will arise, presenting barriers, that stop the caller undertaking effective CPR. Objective: To examine how commonly barriers to telephone CPR occur and whether this affects the time it takes to perform the intervention. Method: A retrospective quantitative analysis was undertaken using a convenience sample of 100 emergency calls. Calls were identified in the emergency control room as cardiac arrests and confirmed by the responding paramedics as cardiac arrests. The calls were listened to, established if CPR instructions were given, if the instructions were followed, if anything hindered the instructions undertaken, and the time taken to reach key points. Findings: 18 cases had bystander CPR administered. An additional 56 of cases had CPR instructions provided but "barriers" in 49% (n = 27) hindered the effectiveness of these. The median time to recognition of cardiac arrest was 40 seconds, with time to first ventilation being 4 min 10 s and time to first compression 5 min 30 s. These times were notably higher in those cases where a barrier to effective telephone CPR existed. Conclusions: Barriers to undertaking telephone CPR occurred with a high degree of frequency. These barriers affect the ability of the caller to perform rapid and effective telephone CPR.